Analysis of Ethernet Over Internet Protocol (EOIP) VPN Performance - Ahmad Purwana (Universitas Putra Indonesia YPTK Padang, 2021)
The need for interconnection between networks will be needed, especially in a company that has many branch offices, but companies usually demand a minimum use of resources in order to get maximum results. To overcome this problem, a Virtual Private Network (VPN) network is needed by utilizing the EOIP protocol, Ethernet Over IP (EOIP) is a protocol on Mikrotik RouterOS which functions to build a network tunnel between Mikrotik routers on a TCP / IP connection, namely by utilizing internet connection as a liaison. This study aims to analyze the performance of VPN by using the concept of Ethernet Over Internet Protocol (EOIP) on the existing network at PT. Energy Source Dempo. This analysis is needed to manage network access to connected data in each branch of the company. This is to anticipate access rights that enter the network owned by PT. Energy Source Dempo. The results of the analysis provide easy access rights and provide a sense of security from the data communication that occurs. In addition, the results of the analysis can also be used as network management control at PT. Dempo Sumber Energi so that the results of the analysis can maximize data communication performance.